Composition of carbonaceous fine particulate emissions of a flexible fuel DISI engine under high velocity and municipal conditions. (15th January 2019) - Miersch, Toni; Czech, Hendryk; Stengel, Benjamin; Abbaszade, Gülcin; Orasche, Jürgen; Sklorz, Martin; Streibel, Thorsten; Zimmermann, Ralf
Graphical abstract: Highlights: High velocity conditions with increased concentrations for particulate constituents. Strong decreased PM emissions by usage of E85. Driving cycle affects quantitative emissions, but not the molecular pattern. Simultaneous quantification of EC, OC and three PAHs. Abstract: A study about the chemical composition of carbonaceous fine particulate emissions of flexible fuel direct injection spark ignition engine under high velocity and municipal conditions was conducted with two different gasoline-ethanol blended fuels (E10 and E85). A self-designed engine test cycle simulating high vehicle velocity conditions of up to of 180 km/h was introduced (high velocity driving cycle, HVDC), simulating a possible motorway scenario without speed legislations as allowed in Germany, and compared to a municipal driving cycle (MDC), which is derived from the New European Driving Cycle (NEDC). The fingerprint of polycyclic aromatic hydrocarbons (PAHs) and their alkylated and oxygenated derivatives as well as the concentrations for PM2.5, elemental carbon (EC), organic carbon (OC) and also for the three most abundant PAHs were determined using a modified thermal optical carbon analyser (TOCA) hyphenated to soft resonance-enhanced multi-photon ionisation mass spectrometry (REMPI-TOFMS). Driving under high velocity conditions resulted in a significant increase of concentrations for PM, EC, OC, methyl-phenanthrenes and pyrene. Engine operation on E85 led to a strong decrease for all concentrations for both cycles. A good correlation was found between concentrations obtained by REMPI-TOFMS and TD-GC/MS. Most prominent PAHs were the alkylated series of phenanthrene, pyrene and naphthalene, whereby the abundances decrease with increasing degree of alkylation. The organic composition between HVDC and MDC mainly differed in quantity and to a lower extent in the aromatic pattern. Nevertheless, methyl-phenanthrenes, pyrene and methyl-pyrenes as well as 4H-cyclopenta[def]phenanthrene and benzo[b]naphtho[1, 2-d]furan/benzo[b]naphtho[2, 3-d]furan and it alkylated series showed a higher abundance in the pattern under high velocity conditions, where alkylated naphthalenes were enhanced in the MDC mode.